Innovation of Binahong (Anredera cordifolia) Seed Extract Indicator Paper as An Alternative in Acid Base Testing - Susilawati, Cica; Sudiarti, Tety; Nuryantini, Ade Yeti (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
The use of synthetic chemicals in acid‒base testing has raised concerns about their environmental impact. The use of natural materials to produce natural indicator paper is an attempt to reduce the negative impact on the environment. Binahong (Anredera cordifolia) seeds can replace conventional chemical synthetic materials. This study aims to develop Binahong seed indicator paper as an alternative environmentally friendly material for acid‒base testing. The method used in this research is experimental and involves the extraction of Binahong seeds, making indicator paper with a certain formulation, and testing the performance of the indicator paper using standard acid and base solutions. Data collection was performed via the observation and measurement of certain parameters. The test results of the Binahong natural indicator paper revealed a significant color change when 95% ethanol was used, which produces a red or purple color at pH 1‒7, a blue color at pH 8‒10 and a yellow color at pH 11‒14. Binahong seeds have potential as an environmentally friendly alternative in acid‒base testing because they respond well to variations in the acidity and basicity of the solution.